Split Common Fixed Point Problem for a Class of Total Asymptotic Pseudocontractions - E. E. Chima; M. O. Osilike (Journal of Applied Mathematics)
We study the split common fixed point problem (SCFP) for a class of total asymptotically pseudocontractive mappings. We obtain some important properties of our class of mappings including the demiclosedness property and the closedness and convexity of the fixed point set. We then propose an algorithm and prove weak and strong convergence theorems for the approximation of solutions of the SCFP for certain class of these mappings.